The rescue of Jews from the Nazi genocide by the inhabitants of Eastern Galicia - Shchupak, Igor (European Spatial Research and Policy, 2021)
The rescue of Jews during the Second World War is one of the least studied issues in the historiography of the Holocaust. The Galicia Region, one of the areas where a total Nazi extermination of Jews occurred, became a region from where a large number of Righteous Among the Nations came – Ukrainians and Poles. The article includes an analysis of the motivations that became the basis for people’s decision to help Jews under the extreme conditions which threatened their lives and the lives of their close ones. It highlights the response of the occupation authorities to rescue actions taken by the non-Jewish population. Despite the unambiguity of the Nazi orders to punish severely those who helped Jews, the real implementation of such sanctions varied. Finally, the article analyses the main determinants (of social, economic, and religious nature) that played an important role in making the decision whether to join the rescue process. The article concludes that no political which could had saved Jews, did lead to any systematic rescue efforts directed at Western Ukrainian Jews, yet the survival of those Jews who were hunter was possible for the deeds of some Polish and Ukrainian people.